ANTIDIABETIC POTENTIAL OF BRACHYLAENA DISCOLOR - Mellem, John Jason; Baijnath, H; Odhav, B (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: The traditional African herbal medicinal system has many reports of anti-diabetic food plants with no known side effects. Such plants and their products have been widely prescribed for diabetic treatment with little known mechanistic basis of their functioning. Therefore, these natural products need to be evaluated scientifically in order to confirm antidiabetic property claims. Materials and Methods: In this study, leaves of Brachylaena discolor were evaluated for potential to inhibit α-amylase and α-glucosidase. The leaves were also screened for toxicity and free radical scavenging capacity. Results: Results from the study show that the methanolic extract gave a higher α-glucosidase inhibition potential and was able to effectively scavenge free radicals better than the aqueous extract. The toxicity, cytotoxicity and mutagenicity screen also showed that both plant extracts are safe for use. Conclusion: These results therefore indicate that B. discolor has the potential for use as a potential dietary adjunct or therapy for the treatment of diabetes.